Identification of a novel selective small-molecule inhibitor of protein arginine methyltransferase 5 (PRMT5) by virtual screening, resynthesis and biological evaluations. Issue 9 (15th May 2018) - Zhu, Kongkai; Jiang, Chengshi; Tao, Hongrui; Liu, Jingqiu; Zhang, Hua; Luo, Cheng
Graphical abstract: Abstract: As one of the most promising anticancer target in protein arginine methyltransferase (PRMT) family, PRMT5 has been drawing more and more attentions, and many efforts have been devoted to develop its inhibitors. In this study, three PRMT5 inhibitors (9, 16, and 23 ) with novel scaffolds were identified by performing pharmacophore- and docking-based virtual screening combined with in vitro radiometric-based scintillation proximity assay (SPA). Substructure search based on the scaffold of the most active 9 afforded 26 additional analogues, and SPA results indicated that two analogues (9 –1 and 9 –2 ) showed increased PRMT5 inhibitory activity compared with the parental compound. Resynthesis of 9, 9 –1, and 9 –2 confirmed their PRMT5 enzymatic inhibition activity. In addition, compound 9 –1 displayed selectivity against PRMT5 over other key homological members (PRMT1 and CARM1 (PRMT4)). While the structure–activity relationship (SAR) of this series of compounds was discussed to provide clues for further structure optimization, the probable binding modes of active compounds were also probed by molecular docking and molecular dynamics simulations. Finally, the antiproliferative effect of 9 –1 on MV4-11 leukemia cell line was confirmed and its impact on regulating the target gene of PRMT5 was also validated. The hit compounds identified in this work have provided more novel scaffolds for future hit-to-lead optimization of small-molecule PRMT5 inhibitors.